The impact of non-pricing tools of revenue management on the performance of hotels in Malaysia - Ahmad, Noor Azmi (2024)
Revenue Management (RM) is a strategic approach that entails allocating appropriate capacity to specific customer segments at optimal prices to maximise revenue. In the past decade, scholarly investigations into hotel revenue management have consistently focused on examining pricing strategies. Even though many studies have been conducted in the field, niche were on the non-pricing aspect of revenue management. Malaysia has exhibited a favorable trajectory in developing hotels and room supply, demonstrating growth from 2015 to 2025. The observation highlights with the increased hotel number of supply led to decreased in hotel revenue per available room (RevPAR). Consequently, hotel organizations must heavily depend on their distribution channels and strategies to sell their room inventory effectively. This study investigates the effects of hotel inventory management practices and distribution channels on revenue management performance (RMP). Non-pricing tools encompass various components, such as hotel inventory management, overbooking strategies, length of stay control mechanisms, room availability guarantees, and distribution channels. It is essential to acknowledge that the classification of distribution channels in this study involved the differentiation between traditional (TDC) and emerging distribution channel (EDC) models to assess their respective impacts on non-financial aspects of hotel performance, focusing on indicators such as average room rate (ARR), occupancy performance, and revenue per available room (RevPAR). In addressing the methodology, the study employed quantitative research by utilising an online survey. The data collected from 120 managers was analysed using the SPSS Statistics version 29 software. Subsequently, the empirical analysis was conducted using SmartPLS 4.0. The analysis method employed in this study was Partial Least Squares Structural Equation Modelling (PLS-SEM).